A business network perspective on local content in emerging African petroleum nations. Issue 4 (7th November 2016) - Owusu, Richard Afriyie; Vaaland, Terje I.
Abstract : Purpose: The paper aims to identify and analyze the actors and their interrelationships in realizing local content objectives in African oil- and gas-producing nations. Design/methodology/approach: The paper includes content analysis of relevant research papers and reports within the oil and gas industry, local content and industrial networks published between 2000 and 2014. Findings: The study developed a framework that integrates the literature on local content with the industrial network theory. The framework classifies the various critical actors for achieving local content, proposing that achieving local content requires the development of business network links and a resource alignment among local companies and institutions and foreign companies and institutions, in addition to multinational oil companies. Research limitations/implications: The framework of this study contributes to an emerging theory on local content by integrating the industrial network theory, which provides specific frameworks for analyzing embedded business environments, along with the previous economic and legal-based studies of local content achievement. Practical implications: The way the relevant actors organize their resources and business networks provides potential for local content in an emerging oil and gas industry in Africa. Originality/value: The paper is one of the few to integrate studies of local content with the industrial network theory. The literature review provides a summary window of the research on the subject over a 14-year period.